Modal Intelektual Hijau terhadap Pengungkapan Emisi Karbon pada Perusahaan Manufaktur di Indonesia - Yanida, Maria; Fitriasari, Pipin; Agustinawati, Ni Putu (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Abstract: Climate change is one of the most significant environmental challenges of the 21st century, raising the global urgency of reducing greenhouse gas emissions. In response, new environmental regulations have emerged to encourage transparency and accountability in environmental impact management, particularly in the corporate sector. In this context, attention to carbon emissions disclosure is increasing, especially as an indicator of a company's commitment to sustainability. This study aims to investigate the influence of green intellectual capital (GIC)—which includes green human capital, green structural capital, and green relational capital—on carbon emissions disclosure in annual reports or company sustainability reports. A quantitative approach is used using secondary data from companies listed on the stock exchange, as well as regression analysis to test the relationship between the dimensions of the GIC and the level of carbon emission disclosure. The results of the study are expected to enrich the literature on the role of green intellectual assets in improving sustainable environmental reporting practices. In addition, these findings could provide practical implications for company management in designing knowledge management strategies and external relationships that support sustainability. Thus, this study not only makes a theoretical contribution, but also serves as a reference for stakeholders in driving GIC integration as part of corporate sustainability strategies. Keywords: Green Intellectual Capital, Carbon Emissions